Implementation of Digital Human Resource Management (E-HRM) to Improve Organizational Efficiency in the Industry 4.0 Era - Hendrawati Hamid (Maneggio, 2025)
This study aims to explore the implementation of Digital Human Resource Management (E-HRM) in improving organizational efficiency in the Industry 4.0 era. E-HRM allows organizations to automate various HR processes such as recruitment, performance management, training, and administration, resulting in operational efficiency and cost reduction. This study uses a qualitative approach with a case study design, relying on in-depth interviews with four informants directly involved in the implementation of E-HRM in their organizations. The results show that E-HRM improves the speed and accuracy of HR processes, enables data-driven decision-making through HR analytics, and reduces operational costs. In addition, E-HRM also increases employee engagement and facilitates skills development. However, implementation challenges such as resistance to change and limited digital skills among employees remain obstacles that need to be overcome with continuous training and strong managerial support. This study provides insights into how E-HRM can improve organizational efficiency, as well as strategies that can be used to overcome challenges in its implementation.